2018
DOI: 10.17271/1980082714320181944
|View full text |Cite
|
Sign up to set email alerts
|

Ureia revestida e o crescimento do cafeeiro arábica

Abstract: Ureia revestida e o crescimento do cafeeiro arábicaCoated urea and the growth of arabica coffee Urea revestida y el crecimiento del café arábigo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The increase in the number of plagiotropic branches is a good indication of an increase in yield, since they are fruit generators. Abranches et al (2018) also observed an increase in the number of plagiotropic branches in coffee plants when evaluated in controlled-release fertilizers compared to those conventional.…”
Section: Discussionmentioning
confidence: 75%
“…The increase in the number of plagiotropic branches is a good indication of an increase in yield, since they are fruit generators. Abranches et al (2018) also observed an increase in the number of plagiotropic branches in coffee plants when evaluated in controlled-release fertilizers compared to those conventional.…”
Section: Discussionmentioning
confidence: 75%